PRODUCT CLUSTERING USING K-MEANS METHOD IN CV. JAYA ABADI - Ika Ramadhaniati (Jurnal TAM (Technology Acceptance Model), 2023)
CV. Jaya Abadi is a company engaged in the distribution of goods, or, to be more precise, a distributor of raw materials for making bread. The fluctuating number of requests from consumers results in stock that must be prepared to be unstable. In addition, many types of products make stock management inaccurate. Sometimes we do not want to have a shortage of stock, goods, or certain products when consumer demand is high. The purpose of this research is to analyse sales data mining through the clustering method with the k-means algorithm. The method used for this analysis uses clustering with the k-means algorithm. So that this research is not subjective, the authors also use research methods in the form of observation, interviews, and documentation. The results of this study were carried out by analysing sales by applying data mining through the clustering method with the k-means algorithm. Data mining that has been going on for a long time can be used as a reference in the management of CV Jaya Abadi. Apart from being used for administrative purposes each period, it can also be used as a decision-making solution in order to maximize existing products and sales at CV Jaya Abadi.